Stiff man syndrome - Meinck, Hans-Michael (CNS drugs, 2001)
Stiff man syndrome (SMS), an uncommon neurological disease, is characterised by symmetrical muscle stiffness and spasms that often lead to skeletal deformity. Variants of the syndrome may involve one limb only (stiff leg syndrome), a variety of additional neurological symptoms and signs such as eye movement disturbances, ataxia, or Babinski signs (progressive encephalomyelitis with rigidity and myoclonus), or be associated with malignant disease (paraneoplastic SMS). Antineuronal autoimmunity and accompanying autoimmune diseases, most often insulin-dependent diabetes mellitus, are characteristic features of SMS and its variants. The condition is frequently misinterpreted as psychogenic movement disturbance, but electromyographic abnormalities and the presence of autoantibodies against glutamic acid decarboxylase (GAD) in both serum and cerebrospinal fluid help to establish the correct diagnosis.
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 04.03.2021